PENGARUH INFLASI, NILAI TUKAR DAN SUKU BUNGA TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2024 - Jannah Andini; Dede Hendra (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the effect of inflation, exchange rate, and interest rate on stock prices of mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research employs a quantitative approach with a purposive sampling technique and panel data analysis using E-Views 13, accompanied by classical assumption tests, hypothesis testing, and the coefficient of determination test. The sample consists of five mining sub-sector companies. The partial test (t-test) results show that inflation (X1) has no significant effect on stock prices (Y), with a probability value of 0.9051 > 0.05. Similarly, the exchange rate (X2) has no significant effect on stock prices (Y) with a probability value of 0.8767 > 0.05, and the interest rate (X3) also has no significant effect on stock prices (Y) with a probability value of 0.6511 > 0.05. The simultaneous test (F-test) also indicates an insignificant result with an F-probability value of 0.367572 (>0.05). The coefficient of determination (R²) value of 0.1368 indicates that only 13.68% of the variation in stock prices can be explained by the three variables, while 86.32% is influenced by other factors outside the model. It is concluded that stock price movements in the mining sector are more dominantly affected by external factors such as global commodity prices rather than domestic macroeconomic conditions.